Optimizing Cryopreservation Protocols for Coffea racemosa and Coffea liberica: Impact of Moisture Content and Packaging on Seed Viability - Stefania Vilas Boas Coelho; Sttela Dellyzete Veiga Franco da Rosa; Lilian Padilha; Janaina Guarieiro Ribeiro de Assis; Ana Luiza de Oliveira Vilela; Ana Maria Oliveira Ferreira; Oliveiro Guerreiro Filho; Masako Toma Braghini (Agronomy, 2024)
Cryopreservation protocols have not yet been defined for seeds of some Coffea species due to their high sensitivity to desiccation and to ultra-low temperatures, factors that lead to low seed survival rates after warming. This reduced rate occurs due to several factors that compromise cellular integrity during the steps of the process. In this study, we evaluated the effect of moisture content and the types of packaging on the cryopreservation of Coffea racemosa and Coffea liberica var dewevrei seeds. For that purpose, seeds were dried to moisture contents of 18, 20, and 25% (dry basis—db) for C. racemosa and to contents of 20, 25, 30, and 35% for C. liberica. The seeds were then packed in mesh bags, Falcon tubes, and triple-laminated aluminum foil pouches before being directly immersed in liquid nitrogen. Physiological and biochemical analyses were performed on the seeds. There was interaction between moisture content and the packaging of the seeds of the species. Drying the seeds to a 20% moisture content and packing them in triple-laminated aluminum foil pouches provided the best cryopreservation protocol among those studied, with survival rates of 79 and 8% for C. racemosa and C. liberica, respectively.